Illustrative example of determining quality of service (QoS) using trustworthiness measurement methodology - Hussain, Farookh; Hussain, Omar; Chang, Elizabeth (IEEE, 2007)
In this paper we make use of a case study comprising of an interaction between a service provider and a service requestor to determine the quality of service (QoS) provided by the service provider. The trustworthiness measurement methodology is made use of to carry out the QoS assessment. The steps involved in the trustworthiness measurement methodology are discussed and illustrated by demonstrating the working of trustworthiness measurement methodology software that we have engineered.